Sodium calcium exchanger operates in the reverse mode in metastatic human melanoma cells - Sennoune, S R; Santos, J M; Hussain, F; Martínez-Zaguilán, R (Cellular and Molecular Biology, 2015)
Cytosolic Ca2+ ([Ca2+]cyt) is important in the regulation of several cellular functions involved in metastasis. We hypothesize that distinct [Ca2+]cyt regulation explains the acquisition of a more metastatic phenotype. To test this hypothesis, we used highly and lowly metastatic human melanoma cells and [Ca2+]cyt was monitored using Fura-2AM and fluorescence spectroscopy. Stimulation with ATP elicited a sustained increase in [Ca2+]cyt in highly metastatic cells, but a transient increase in lowly metastatic cells. Na+ substitution revealed Na+/Ca2+ exchanger (NCX) activity in reverse mode in highly, but not in lowly metastatic cells. In highly metastatic cells, addition of Na+ in the plateau phase of [Ca2+]cyt increase elicited with ATP, in the absence of Na+, resulted in a rapid return to basal, indicating that NCX can operate in both reverse and forward modes. Inhibition and knockdown of NCX, using KB-R7943 and siRNA NCX-1 respectively, supported the significance of NCX in [Ca2+]cyt regulation in highly metastatic cells. Stimulation with UTP triggered a rapid increase in highly metastatic cells [Ca2+]cyt, but not in lowly metastatic cells suggesting that highly and lowly metastatic cells exhibit distinct purinergic receptors. These data indicate that following agonist-stimulation, NCX operates preferentially in the reverse mode to enable a sustained [Ca2+]cyt increase in highly metastatic cells. The forward mode of NCX operation to extrude Ca2+ is preferred in lowly metastatic cells. The acquisition of a more metastatic phenotype involves a switch in NCX activity from forward to reverse mode that is favorable to maintain elevated [Ca2+]cyt in response to agonist stimulation.